Wskaźnik korzyści środowiskowych w ocenie ekonomicznej efektywności inwestycji w odnawialne źródła energii - Ligus, Magdalena (Environmental Benefits Indicators in the Assessment of Economic Effectiveness of Investments in Renewable Energy Sources, 2009)
The paper concerns methodological aspects of economic effectiveness of renewable energy projects assessment, based on cost-benefit analysis (CBA), focusing on the valuation of environmental benefits from renewable energy production. The empirical research results of valuing benefits from improving air quality in Poland using contingent valuation method (CVM) are presented. The survey was held on all-Polish sample of adults in cooperation with professional public opinion research centre. The main goal of the research was to find the household's average monthly willingness to pay in addition to electricity bill in order to improve air quality in Poland. The research finally was used to estimate the environmental benefits indicator from renewable energy production, after the procedure proposed by the author. The result of the original research was confronted with the alternative research conducted with benefit transfer method on the basis of methodology of European Commission's ExternE (External Costs of Energy) project. The conclusions on the financial and economic effectiveness of renewable energy projects are supported with the results of case studies of wind power plant, biomass heat-generating plant and biogas power plant.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 166-177